Rancang Bangun Marketplace Berbasis Website menggunakan Metodologi Systems Development Life Cycle (SDLC) dengan Model Waterfall - Ridwan, Muhammad; Fitri, Iskandar; Benrahman, Benrahman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The purpose of designing this marketplace is to take part in enlivening the potential of the e-commerce market or online stores in the Indonesian market. The SDLC methodology is used as a process of making and modifying the system and has structured stages from System planning, System Analysis, System Design, System Implementation, System Testing & System Maintenance. The result of this Marketplace Design is as a forum to make it easier for sellers or shop owners in the fields of Computers, Gadgets, Electronic Games, and the like to market their products.Keywords:Design, Marketplace, Methodology SDLC, Model Watefall.